2005
DOI: 10.1345/aph.1e577
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol Exposures Reported to Statewide Poison Control System

Abstract: Tramadol overdoses frequently cause CNS depression, nausea/vomiting, tachycardia, and seizures. Symptoms generally resolve within 24 hours. Accidental ingestions in children were well tolerated, primarily causing sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
102
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 13 publications
(7 reference statements)
18
102
4
1
Order By: Relevance
“…In the present study, time of seizure varied from 20 min to 12 h post-ingestion; however, 95% of seizures occurred in the first 6 h after ingestion, which is in agreement with studies conducted by Mehrpour et al [28], Marquardt et al [27], Jovanović-Cupić et al [24], and Talaie et al [9].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, time of seizure varied from 20 min to 12 h post-ingestion; however, 95% of seizures occurred in the first 6 h after ingestion, which is in agreement with studies conducted by Mehrpour et al [28], Marquardt et al [27], Jovanović-Cupić et al [24], and Talaie et al [9].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the smallest reported dose associated with seizure was 200 mg (was seen in four patients). This is lower than previously published studies, in which the smallest dose of tramadol-associated seizure was reported to be 300 mg [5,27].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Some studies noted occurrence of seizure even in recommended doses [14,21]. Spiller et al studied 87 patients with tramadol poisoning and described seizures in 7 (8%) [20].…”
Section: Discussionmentioning
confidence: 99%
“…The neurotoxicity of tramadol mainly occurs within 24 hours postingestion, and 84.6% of seizures occur within 6 hours after tramadol intake. The minimum dose of tramadol that induces seizure has been reported to be 200 mg in two different studies [14,15]. The aim of this study was to evaluate the incidence of seizure among users and abusers of tramadol.…”
Section: Introductionmentioning
confidence: 99%